JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
Omphalomesenteric duct cysts are uncommon congenital anomalies and may present with nonspecific abdominal symptoms in children. We report a 6-year-old girl who presented with acute periumbilical pain and recurrent vomiting. Ultrasonography revealed an infraumbilical cystic lesion, dilated small-bowel loops, and a band-like echogenic structure that appeared to extend from the inferior aspect of the cyst toward an adjacent dilated bowel loop. Computed tomography confirmed small-bowel obstruction and provided a broader cross-sectional view of the infraumbilical cyst and the posterior course of the band-like structure. Surgical exploration confirmed that the fibrous band arose from the inferior aspect of the omphalomesenteric duct cyst and extended to the ileum, causing mechanical small-bowel obstruction. This case highlights the value of ultrasonography in the preoperative demonstration of the complete cyst-band-bowel relationship.